2017
DOI: 10.1016/j.pharep.2017.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Vortioxetine: A review of the pharmacology and clinical profile of the novel antidepressant

Abstract: The aim of this paper was to review the up-to-date evidence base on pharmacology and clinical properties of vortioxetine. Vortioxetine is a novel antidepressant, approved by the US Food and Drug Administration (FDA) for the treatment of major depressive disorder (MDD). Because vortioxetine exhibits both an antidepressant and anxiolytic effect, it may be effective in treating both depressive and anxiety disorders, such as generalized anxiety disorder (GAD). Based on its pharmacodynamics profile and preclinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 51 publications
0
46
1
1
Order By: Relevance
“…Theoretically, the concomitant use of vortioxetine and an SSRI may boost serotonergic activity without further postsynaptic 5-HT 2A blockade (thus limiting the SSRI dose-related side effects). 16,26 Moreover, the partial agonist effect of vortioxetine on the postsynaptic 5HT 1B heteroreceptors located in GABAergic interneurons may increase the release of glutamate in the hippocampus and prefrontal cortex, which may further contribute to an antidepressant effect. 27 This mechanism of action may also increase clinical efficacy in treating cognitive symptoms, which are frequently present in patients with suboptimal or inadequate response to antidepressants, and thus contribute to the achievement of complete remission in everyday clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, the concomitant use of vortioxetine and an SSRI may boost serotonergic activity without further postsynaptic 5-HT 2A blockade (thus limiting the SSRI dose-related side effects). 16,26 Moreover, the partial agonist effect of vortioxetine on the postsynaptic 5HT 1B heteroreceptors located in GABAergic interneurons may increase the release of glutamate in the hippocampus and prefrontal cortex, which may further contribute to an antidepressant effect. 27 This mechanism of action may also increase clinical efficacy in treating cognitive symptoms, which are frequently present in patients with suboptimal or inadequate response to antidepressants, and thus contribute to the achievement of complete remission in everyday clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, it was found that inhibition of SERT as well as the 5-HT 1B receptor increases the serotonin concentration in the prefrontal cortex, while agonists of this receptor increase the rate of firing of serotonergic neurons in the raphe nucleus [33]. This research direction allows new drugs to be introduced into the clinic, e.g., vortioxetine [34]. In presented study on the affinity of Cr(III) to selected receptors and transporters, no affinity to SERT, α 1 , and β 1 was found; very poor activity was determined in relation to the 5-HT 1A receptor.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most recently registered AD widely modulates neurotransmission in the CNS directly through serotonin receptors, and indirectly through other pathways [77]. It is considered one of the fastest-acting AD with first effects that can be seen after two weeks of therapy [78]. Despite proven anxiolytic properties, it seems that the drug is more activating in nature, especially in the first period of use, which may translate into a lack of sleep-regulating or anxiolytic effect during this period, and consequently no improvement felt by the patient until the antidepressant effect of the drug is activated [79,80].…”
Section: Vortioxetinementioning
confidence: 99%
“…Najnowszy spośród zarejestrowanych w Polsce leków przeciwdepresyjnych wykazuje szeroko moduluje neuroprzekaźnictwo w OUN bezpośrednio poprzez receptory serotoninowe, a pośrednio poprzez pozostałe szlaki [77]. Jest uznawany za jeden z najszybciej działających AD z pierwszymi efektami, które mogą być widoczne już po 2 tygodniach terapii [78]. Mimo udowodnionego działania przeciwlękowego, wydaje się, że lek ma bardziej charakter aktywizujący, zwłaszcza w pierwszym okresie stosowania, co przekłada się na brak efektu regulującego sen lub anksjolitycznego w tym okresie, a w konsekwencji brak odczuwalnej przez pacjenta poprawy do momentu uaktywnienia się działania przeciwdepresyjnego leku [79,80].…”
Section: Farmakoterapia Depresji -Założenia Ogólneunclassified